Unveiling the Potential of Fungal Endophytes for Abiotic Stress Mitigation in Wheat: Fungal endophytes for abiotic stress mitigation in wheat - H.M., Mamrutha; Wadhwa, Zeenat; RR, Abhishek; AS, Padmaja; Shetty, Neekshitha; Preety Rani,; Ahlawat, OP; Tiwari, Ratan; Karaba N, Nataraja (Journal of Cereal Research, 2025)
The study investigates the role of endophytic fungi in enhancing wheat tolerance to abiotic stresses, a critical area of research in the context of global climate change and food security. Fungal endophytes are known to support plant health and productivity under stress conditions. In this work, we explored the effects of two stress-tolerant fungal endophytes on wheat growth and abiotic stress mitigation. The experiments were conducted at the Indian Council of Agricultural Research–Indian Institute of Wheat and Barley Research (ICAR–IIWBR), Karnal. Our results provide evidence that these endophytes significantly improve stress adaptive traits in wheat, with potential implications for sustainable agriculture across diverse agroecological zones. We believe this study offers valuable insights for enhancing wheat resilience and contributes to the broader goal of ensuring food security under changing environmental conditions.